2004
DOI: 10.1111/j.1939-1676.2004.tb02635.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary (n‐3) Fatty Acids from Menhaden Fish Oil Alter Plasma Fatty Acids and Leukotriene B Synthesis in Healthy Horses

Abstract: The study objective was to determine the effect of feeding corn oil or fish oil to horses on plasma fatty acid profiles and leukotriene B (LTB) synthesis by stimulated peripheral blood neutrophils. Two groups of horses (n = 5) were randomly assigned to diets supplemented with either 3.0% (by weight) corn oil or fish oil for a period of 14 weeks. The ratio of (n‐6) to (n‐3) fatty acids in oil supplements was 68.1:1 for corn oil and 0.12:1 for fish oil. Production of LTB4 and LTB5 by peripheral blood neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
4
14
2
Order By: Relevance
“…An amplified plasma concentration of n-3 PUFA was observed following FO consumption for 14 days in this study, which agreed well with the previous study in horses by Hall et al [19]. Hall et al [19] also found decreased plasma n-6 FA concentration in the FO-fed horses, but little variation of plasma n-6 PUFA concentration was observed in the FO-fed rats in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…An amplified plasma concentration of n-3 PUFA was observed following FO consumption for 14 days in this study, which agreed well with the previous study in horses by Hall et al [19]. Hall et al [19] also found decreased plasma n-6 FA concentration in the FO-fed horses, but little variation of plasma n-6 PUFA concentration was observed in the FO-fed rats in this study.…”
Section: Discussionsupporting
confidence: 92%
“…An amplified plasma concentration of n-3 PUFA was observed following FO consumption for 14 days in this study, which agreed well with the previous study in horses by Hall et al [19]. Hall et al [19] also found decreased plasma n-6 FA concentration in the FO-fed horses, but little variation of plasma n-6 PUFA concentration was observed in the FO-fed rats in this study. Noting that the horses used in the study of Hall et al [19] consumed FO for 6 weeks, a shorter consumption period (24 days) in this study may explain the little variation of n-6 PUFA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Equine neutrophils, collected from a healthy horse that was not included in this study, were purified from whole blood with heparin added as an anticoagulant, using a histopaque 1119 density gradient centrifugation protocol as previously described. 14 More than 93% of total cells isolated were neutrophils, and cell viability was greater than 90% based on trypan blue exclusion. These neutrophils were resuspended in Earle's minimum essential medium (EMEM; with 25 mm N-2-hydroxyethylpiperazine-N9-2-ethanesulfonic acid (HEPES) buffer without L-glutamine and phenol red) with 5% heatinactivated fetal calf serum (FCS).…”
Section: Methodsmentioning
confidence: 99%
“…In arthritic horses, supplementation with EPA and DHA increased stride length (Woodward et al, 2005) and reduced inflammatory markers (Manhart et al, 2009). In horses, feeding Menhaden fish oil modulated leucotriene synthesis influencing inflammatory conditions (Hall et al, 2004).…”
Section: Sources Of Fatty Acids In the Dietmentioning
confidence: 99%